Orthopedic emergencies : - Haig, Scott Vanderwink (McGraw-Hill, 2005)
Haig (orthopedic surgery, Columbia University) and Flores (emergency medicine, Lawrence Hospital) present an atlas for spotting and treating fractures. Arranged anatomically, the beginning of each section shows the normal X-rays for that body part with the bones and key joint structures labeled. Next is a list of problems found, from the most common to the least, with the radiographic or physical examination clue to expect with them. Treatment bullets accompany photos and X-rays to remind clinicians of essentials of emergency treatment for this particular injury.